Analysis of the Utilization of Productive Zakat Funds on Mustahiq Income in Baznas Bone Regency - Akifah; Sitti Nikmah Marzuki; Muh. Arafah (Institut Pendidikan Alfatah Mataram, 2024)
The purpose of this research is to find out the management of productive zakat in baznas bone district and the utilization of productive zakat in supporting mustahiq income. This research uses field research using qualitative research with a descriptive approach. The data in this research was obtained through direct observation and interviews at the Bone Regency Baznas Institution and also mustahiq who have been given assistance. The results of this study indicate that Baznas Bone Regency collects zakat from muzakki and makes efforts to provide assistance to people who are unable to improve the standard of living of mustahiq, this is realized with a work program in the field of distribution, namely the humanitarian field, the economic field, the education field, the health field, and the field of da'wah and advocacy. In this case Baznas Bone Regency has not worked optimally. In carrying out its duties, the workforce is small or limited, which hinders the performance of Baznas Bone Regency.